Aplicação de técnicas contemporâneas de ressonância magnética nuclear no estudo fitoquímico de Aspidosperma ulei Markgf - Uchoa, Daniel Esdras de Andrade (2006)
The material (root and stem) of Aspidosperma ulei Markgf (Apocinaceae), popularly known as Pitiá, was collected in the locality of Garapa, Acarape County, Ceará. In this work, aliquots of the ethanol extracts of the root and of the stem barks of A. ulei were submitted to chromatographic analysis in sephadex and silica gel , and CLAE, making possible the isolation of the alkaloids (+)-20(S)uleíne (AU-1). (+)-20(S)-dasicarpidone (AU-2), (-)-16, 19-dimethyl-3, 5, 14, 21-tetra-hydro-ellipticine (AU-3), (-)-β-yohimbine (AU-4), (-)-20(S)-N-demethyl-uleine (AU-5), (+)-15(S)-18-hidroxy-20(Z)-16, 17-nor-subincanadine E (AU-7) and (+)-15(S)-20(Z)-16, 17-nor-subincanadine E (AU-8), and a inositol derivative, the (-)-D-1-O-methyl-myo-inositol (AU-6). The alkaloid, (+)-15(S)-18-hidroxy-20(Z)-16, 17-nor-subincanadine E (AU-7) and (+)-15(S)-20(Z)-16, 17-nor-subincanadine E (AU-8) are related for the first time as natural product, but the last one has been characterization as an intermediary of the Stryenos’ alkaloids synthesis. The identification and characterization of the isolated compounds was accomplished by IR and 1D and 2D NMR techniques, mainly contemporary techniques as edited HSQC, HSQC-TOCSY and 1H,X-HMBC (X = 13C or 15N). Pharmacological studies of an alkaloid rich fraction of the root bark of A. ulei, accomplished in the Departamento de Fisiologia e Farmacologia da UFC by Prof. V. S. N. Rao. Demonstrated the pro-erectile effect of that fraction in three cases: penile erection, erection-like and genital grooming in mice. Intraperitoneal injection of the fraction (25 to 50 mg/Kg), shown all three different responses similar to yohimbine (2 mg/Kg). This study further supports the traditional use of extracts from Aspidosperma species in erectile dysfunctions.